2015
DOI: 10.1093/jscr/rjv033
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic giant cystic lymphangioma of the liver in an adult female

Abstract: An 18-year-old woman who presented with epigastric pain was diagnosed with rupture of a hepatic tumor and transported to our hospital. Contrast-enhanced computed tomography revealed a 13-cm, low-density giant mass in the left hepatic lobe and high-density ascites, indicating abdominal bleeding from the liver tumor. The patient underwent emergent celiac angiography, and the left hepatic artery, which was believed to feed the tumor, was embolized. After the patient's condition stabilized, she underwent left hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The hepatic lymphatic malformations produce varying signals in T1- and T2-weighted sequences, depending on the quantity of fat and fluid components [ 30 ]. Lympho-MR sequences can show dilated lymph duct surrounding the lesion, thereby supporting the diagnosis of HLM [ 25 , 28 ]. Finally, hepatic lymphatic malformations can spontaneously disappear (Fig.…”
Section: Other Cystic Lesionsmentioning
confidence: 99%
“…The hepatic lymphatic malformations produce varying signals in T1- and T2-weighted sequences, depending on the quantity of fat and fluid components [ 30 ]. Lympho-MR sequences can show dilated lymph duct surrounding the lesion, thereby supporting the diagnosis of HLM [ 25 , 28 ]. Finally, hepatic lymphatic malformations can spontaneously disappear (Fig.…”
Section: Other Cystic Lesionsmentioning
confidence: 99%
“…The morphology was enough to make the diagnosis for most cases[ 13 , 31 ]. Certainly, lymphatic marker, D2-40 (podoplanin), further confirmed the identification of the disease[ 1 , 19 , 32 ]. In addition, endothelial markers, including von Willebrand factor, CD31, and CD34 and two lymphatic markers, LYVE-1 and Prox-1, are recommended through immunohistochemistry staining when it is difficult to distinguish lymphatic vessels from blood vessels[ 1 ].…”
Section: Discussionmentioning
confidence: 89%
“…Based on the reviewed literature (Table 1 ), hepatic lymphangioma could be presented at any age from newborns to the elderly (average age is 30 years)[ 19 , 20 ]. In our case, the patient was a 50-year-old female.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review of the literature identified 23 cases of solitary hepatic lymphatic malformations from 1994 to 2020 (13 males and 10 females), with an age range from 22 days to 75 years [ 15 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. According to our review, the management of symptomatic LMs of the liver is still predominantly based on surgical resection [ 15 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , 38 , 40 , [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. This can be explained by the fact that the cases described concerned LMs with well-defined profiles and sufficiently distant from vascular or nerve structures, for which surgical approach could guarantee a complete resection and important neurovascular structures sparing.…”
Section: Management and Treatment Optionsmentioning
confidence: 99%